Exploring the Socioeconomic Factors Influencing Savings for the Future in Poland - Domańska, Julia (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The rapid pace of modern changes has profoundly impacted Polish society, with adverse demographic shifts posing a significant challenge to long-term financial sustainability. The possibility of obtaining an insufficient amount of financial resources resulting from the benefit poses the necessity of taking care of one’s future on one’s own after the end of one’s professional career. In the face of current challenges, understanding the factors influencing the decision to save for the future becomes an important element. Aim: The study aims to identify variables that significantly influence the probability of saving for the future. Results: Using logit models, an analysis of data on 509 respondents from Poland was conducted. The results indicate that younger people are more likely to take the initiative to save for the future compared to a group of people who are at the end of their careers. In addition, factors such as a higher level of education, higher income, or salary satisfaction significantly increase the decision to save for the future. An analogous situation exists among those who have sustainable consumer spending, i.e., they do not allocate all of their current income growth to consumer spending. In addition, people who are convinced of their ability to accumulate funds for a higher pension on their own are more likely to undertake saving for the future. The results suggest that efforts should target younger generations with lower income levels and education. Raising financial awareness and encouraging sustainable financial management can contribute to having enough money for retirement in the face of current demographic challenges. The results obtained can form the basis for the development of optimal, effective educational strategies and financial incentives that would ensure the financial security and stability of citizens at the end of their working lives. Keywords: pension system, saving, demographics, logit models JEL: C01; E21; J26